Cellular uptake, transport mechanism and anti-inflammatory effect of cyanidin-3-glucoside nanoliposomes in Caco-2/RAW 264.7 co-culture model - Yang, Mengyu; Lu, Xiaoqin; Xu, Jie; Liu, Xiaofeng; Zhang, Wei; Guan, Rongfa; Zhong, Hao (Frontiers in Nutrition, 2022)
Cyanidin-3-glucoside (C3G), which is the widest and richest anthocyanin (ACN) in the edible fruit and vegetables, has been illustrated to perform a wide range of bioactivities. Nanoliposomes, as carriers for conveying drugs or small molecules to specific sites, can prevent C3G molecules from degradation and enhance the absorption rate of C3G. To date, the bioavailability, bioactivity and transport mechanism of C3G nanoliposomes are still unknown. This study aims to explore the uptake, transport and anti-inflammatory effects of C3G nanoliposomes in Caco-2/RAW264.7 co-culture model, which symbolizes an intestinal inflammation model. The results showed that the uptake and transport of C3G nanoliposomes by Caco-2/RAW264.7 co-culture model were concentration-dependent as well as affected by temperature (37 and 4℃) and endocytic inhibitors, which revealed C3G nanoliposomes penetrate cells via endocytosis. Moreover, compared with C3G, C3G nanoliposomes significantly decreased pro‐inflammatory cytokine (TNF-α, IL-1β, IL-6, IL-8) expression, suggesting a stronger anti-inflammatory potential. Conclusively, the uptake of C3G nanoliposomes by Caco-2/RAW264.7 co-culture model is mainly involved in macropinocytosis and endocytosis mediated by carrier protein (clathrin). C3G nanoliposomes may play a better role in the treatment of LPS-induced intestinal inflammation diseases.